(S)-Thienyl and (R)-Pirydyl phosphonate Derivatives Synthesized by Stereoselective Resolution of Their Racemic Mixtures With Rhodotorula mucilaginosa (DSM 70403) - Scaling Approaches - Lubiak-Kozłowska, Katarzyna; Brzezińska-Rodak, Małgorzata; Klimek-Ochab, Magdalena; Olszewski, Tomasz K.; Serafin-Lewańczuk, Monika; Żymańczyk-Duda, Ewa (Frontiers in Chemistry, 2020)
Rhodotorula mucilaginosa was successfully applied as biocatalyst for the enantioselective resolution of the racemic mixtures of heteroatom phosphonates derivatives, what resulted in receiving the following enantiomers: (S)-1-amino-1(2-thienyl)methylphosphonic acid (Product 1) and (R)-1-amino-1-(3’pirydyl)methylphosphonic acid (Product 2). Biological synthesis of both products is reported for the first time. Pure (S)-1-amino-1-(2-thienyl)methylphosphonic acid (Product 1) was isolated with conversion degree of 50% after 24hrs of biotransformation conducted on laboratory scale under moderate conditions (1.55 mM of substrate 1, 100 mL of distilled water, 135 rpm, 25 C; Method A). The scale was enlarged to semi-preparative one, using simplified flow-reactor (Method C; 3.10 mM of substrate 1) and immobilized biocatalyst. Product was isolated with 50% of conversion degree just after 4hrs of biotransformation. Amino-1-(3’pirydyl)methylphosphonic acid (Substrate 2) was converted according to novel procedure, by immobilized biocatalyst - Rhodotorula mucilaginosa. Process was carried out under moderate conditions (3.19 mM – substrate 2 solution; Method C1) with the application of simplified flow reactor system, packed with the yeasts biomass entrapped in 4% agar-agar solution. Pure (R)-amino-1-(3’pirydyl)methylphosphonic (50% of conversion degree) was received within the only 48hrs.